1988
DOI: 10.1042/bj2500363
|View full text |Cite
|
Sign up to set email alerts
|

α-adrenergic suppression of very-low-density-lipoprotein triacylglycerol secretion by isolated rat hepatocytes

Abstract: The effect of adrenaline on triacylglycerol synthesis and secretion was examined in isolated rat hepatocytes. Cells were incubated with 0.5 mM-[1-14C]oleate, and the accumulation of triacylglycerol and [14C]triacylglycerol was measured in the incubation medium. Triacylglycerol appearing in the medium was present in a form with properties similar to very-low-density lipoproteins. Triacylglycerol, [14C]triacylglycerol and [14C]phospholipid contents of hepatocytes were also determined. Addition of 10 microM-(-)ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…15,16 It has been shown that adrenaline suppresses the secretion of VLDL-TAG in isolated rat hepatocytes and that this effect is mediated by the a 1 adrenergic receptor. 17,18 Similar results were obtained in a model of perfused liver, in which noradrenaline decreased the secretion of TAG and apoB. 19 A previous study by our group demonstrated decreased capacity of fatty acid oxidation and the incorporation of lipid in the VLDL secreted by denervated livers.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…15,16 It has been shown that adrenaline suppresses the secretion of VLDL-TAG in isolated rat hepatocytes and that this effect is mediated by the a 1 adrenergic receptor. 17,18 Similar results were obtained in a model of perfused liver, in which noradrenaline decreased the secretion of TAG and apoB. 19 A previous study by our group demonstrated decreased capacity of fatty acid oxidation and the incorporation of lipid in the VLDL secreted by denervated livers.…”
Section: Introductionsupporting
confidence: 77%
“…4,25 Previous studies in our laboratory had already shown that hepatic denervation alters lipid metabolism in the organ, leading towards lower oxidation of fatty acids and decreased incorporation into VLDL. 20 It is known that catecholamines play a role in the regulation of VLDL secretion, 17,19,26 but no studies, to our knowledge, have so far examined the importance and contribution of the sympathetic innervation to the process. Our results show a lower secretion of VLDL in the denervated animals compared with controls, which was related with a lower expression of apoB in these.…”
Section: Discussionmentioning
confidence: 98%
“…It is not clear why hepatic TG secretion decreased at FiO 2 ϭ 0.10, although we exonerated transcriptional changes in MTP or apoB. Perhaps catecholamines played a role, since epinephrine has been shown to suppress VLDL secretion (9,13). Why does acute hypoxia decrease VLDL secretion while chronic IH apparently augments it (39)?…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, glucagon, in terms of its activation of AMPdependent protein kinase, could effect apoB phosphorylation similarly to that described for acetyl-CoA carboxylase [49] and HMG-CoA reductase [50]. Glucagon may also act via'changes in intracellular Ca21 concentration [51] and, in this respect, it has previously been shown that a-adrenergic stimulation of hepatocytes, which results in a redistribution of intracellular Ca2+, also inhibits VLDL triacylglycerol secretion [52]. Although the shorter-term effects (i.e.…”
Section: Discussionmentioning
confidence: 99%